2013
DOI: 10.1039/c3sc50419k
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael additions of α-cyanoacetates by soft Lewis acid/hard Brønsted acid catalysis: stereodivergency with bi- vs. monometallic catalysts

Abstract: The direct asymmetric conjugate addition of a-cyanoacetates to enones generating densely functionalized a-amino acid precursors with adjacent quaternary and tertiary stereocenters is described comparing monoand bis-palladacycle catalysts. This edge article features the complementary value of mono-and bimetallic catalysis in a case study using related catalyst systems. Different major diastereomers of the 1,4-addition products are formed by the use of the planar chiral mono-and bimetallic catalyst systems and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…As a model reaction we initially chose the AAA of α‐phenyl methyl ester 1a ‐Me with the parent allyl acetate 2a (Table 1). In previous investigations our research group has already shown that metallocene‐derived bis‐palladacycles are capable of activating α‐cyanoacetates for enantioselective 1,4‐addition reactions 7a,10. In addition we have reported electrophilic olefin activations with these bis‐palladacycles11 and related platinum catalysts,12 which includes allylic imidate rearrangement reactions 13,14.…”
Section: Resultsmentioning
confidence: 99%
“…As a model reaction we initially chose the AAA of α‐phenyl methyl ester 1a ‐Me with the parent allyl acetate 2a (Table 1). In previous investigations our research group has already shown that metallocene‐derived bis‐palladacycles are capable of activating α‐cyanoacetates for enantioselective 1,4‐addition reactions 7a,10. In addition we have reported electrophilic olefin activations with these bis‐palladacycles11 and related platinum catalysts,12 which includes allylic imidate rearrangement reactions 13,14.…”
Section: Resultsmentioning
confidence: 99%
“…By treatment of 3.6 mmol of 1 a and 3.5 mmol of 2 a in the presence of 0.01 mol % L 2 ‐RaPr 3 /Mg(OTf) 2 complex, 1.08 g 3 a was obtained with 92 % ee (95 % yield, Scheme a). The product could also be reduced by Cp 2 TiCl 2 in situ, and then further converted efficiently to α‐amino amide 5 a and 1,2‐diamine 6 a by treating with H 2 O 2 and NaBH 4 , respectively (Scheme b). The convenient gram‐scale synthesis in low catalyst loading and useful transformations indicated a potential of this methodology in medicinal chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…Scheme 39 Michael additions of α-cyanoacetates [177] Scheme 40 Asymmetric intramolecular Friedel-Crafts allylic alkylation of phenols [190] Q. Sha et al…”
Section: Friedel-crafts Reactionsmentioning
confidence: 99%
“…The challenges that remain are the applicability of the various classes Scheme 36 Asymmetric synthesis of spirooxindoles by a Mannich-type reaction of isothiocyanato oxindoles [161] Scheme 37 Michael addition of 3-alkylidene oxindoles to chalcones [172] Scheme 38 Michael addition/protonation of thiols with enones [175] The Future of Catalysis by Chiral Lewis Acids of α,β-unsaturated Michael acceptors (e.g., ketones, esters, amides, nitro compounds), with suitable Michael donors and catalyst, and adding to this array of variables the solvent presents opportunities that appear today as a multidimensional problem for which there are few guidelines. A bis-palladacycle, (FBIPCl) 2 , is a new chiral catalyst that has recently been introduced [176][177][178] as an effective catalyst (after activation by chloride abstraction with a silver salt) for Michael addition to α,β-unsaturated ketones (e.g., Scheme 39) by α-carbonyl-stabilized nucleophiles. These reactions occur with bimetallic activation and exhibit relatively low catalyst loading.…”
Section: Michael Reactionsmentioning
confidence: 99%